Writing as Therapy and Meaning in Our Previous Life by Anne-Sophie Brasme - Кобчінська, Олена Іванівна (Київський національний університет імені Тараса Шевченка, 2024)
Background. The article regards specifics of a fictional narrative on trauma from the perspective of self-writing by a fictional character. Based on a range of concepts of storytelling as a means of constructing one's identity, an instrument of dealing with posttraumatic consequences, and a form of recovering memory lacunes, formulated by literary critics (Ph. Lejeune, J. Derrida, J. Pavlenko), philosophers (P. Ricoeur), as well as sociologists (J.-C. Kaufmann, A. Giddens), it has been attempted to analyze self-writing strategies as a psychanalytical quest performed by characters in a novel by a contemporary French writer Anne-Sophie Brasme Our previous life (2014). Several conclusions have been made on therapeutic, cathartic, and cognitive impacts within different types of self-writing strategies of the female protagonist (namely, diary and novels by her). Methods. The study primarily aims to integrate the concept of narrative identity proposed by a French philosopher Paul Ricoeur who conceives narrative as an instrument of overcoming the gap between basic philosophical categories, in particular selfhood and identity, as well as apply it in relation to the construction of the narrative identity of the heroine-writer, who experiences deep trauma throughout her life. The analysis of the work uses the personal concept of the French sociologist J.-K. Kaufmann, for whom the narrative in the light of writing about oneself is not only a powerful means of storytelling, but also a tool of for building life perspective through making key choices suggested by narration on oneself. These concepts are revealed on the example of the mechanics of writing on oneself of the main character of the novel chosen for analysis against the background of theses assumed by Philip Lejeune, Jacques Derrida, and Anthony Giddens. Results. The study aims to reveal the life path of the female heroine as a writer, who chooses writing as a way of both escaping from reality and experiencing her trauma be rediscovering it throughout writing about traumatic past. It is concluded that as the heroine thrives towards her past, whereas a clearer perspective of her present and future is built, where writing on oneself appears as a precious key guide between those opposed layers of her hearting psyche Conclusion. Based on the results of the research, several generalizations are made allowing us to reveal the therapeutic and meaning-making role of artistic writing as a powerful mean of living deeply traumatic experience.

Вступ. Розглянуто специфіку художнього наративу про травму з позицій письма про себе персонажа ху-дожнього твору. З опертям на деякі концепції оповіді про себе як конструювання ідентичності, інструменту подолання посттравматичних розривів психіки та форми подолання лакун у пам'яті, сформульовані в дороб-кові літературознавців (Ф. Лежен, Ж. Дерида, Ю. Павленко), філософів (П. Рікер) і соціологів (Ж.-К. Кауфманн, Е. Ґідденс), зроблено спробу розглянути художнє письмо як спосіб терапевтичного квесту персонажів роману сучасної французької письменниці Анн-Софі Брасм "Наше попереднє життя" (2014). Зроблено багато узагальнень щодо терапевтичної, катарсичної та смислотворчої функцій окремих первнів щоденникового та художнього письма героїні-письменниці у творі. Методи. У дослідженні використано концепцію оповідної ідентичності французького філософа Поля Ріке-ра, який осмислює наратив як інструмент подолання розриву між засадничими філософськими категоріями, зокрема самістю та тотожністю, і застосовано її у стосункові до конструювання оповідної ідентичності геро-їнею-письменницею, що переживає глибинну травму впродовж свого життя. Під час аналізу твору використано, зосібна, концепцію французького соціолога Жана-Клода Кауфманна, для якого наратив у світлі письма про себе виступає не лише потужним засобом сторітелінгу, але й інструментом конструювання власного життєвого шляху через реалізацію людиною того чи іншого доленосного вибору, навіяного їй оповіддю про саму себе. Ці концепції розкрито на прикладі механіки письма про себе головної героїні обраного для аналізу роману на тлі наукових узагальнень Філіпа Лежена, Жака Дериди, Юлії Павленко та Ентоні Ґідденса. Результати. Під час дослідження проаналізовано життєвий шлях героїні як письменниці, що обирає пи-сьмо одночасно способом втечі від реальності та інструментом переживання своєї травми. Зроблено висно-вок, що мірою того, як героїня відкривається назустріч своєму минулому, вибудовується ясніша перспектива її сучасного і майбутнього, у яких письмо про себе постає цінним провідником між конфліктуючими пластами її травмованої психіки. Висновки. На основі результатів дослідження зроблено багато узагальнень, що дозволяють оприявити терапевтичну та смислотворчу роль художнього письма на шляху героїні-письменниці до проживання травма-тичного досвіду.
Письмо як терапія і сенс у романі Анн-Софі Брасм "Наше попереднє життя"
Keywords: автобіографія; письмо про себе; студії травми; сучасна французька література; теорія ідентичності; фікційний суб'єкт художнього письма; autobiography; fictional subject of artistic writing; identity theory; modern French literature; self-writing; trauma studies